Analysis of Badminton Techniques Smash Using a Biomechanical Approach: Systematic Literature Review - Salisa Zafirin Nuri Artazila; Adi S (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Study purpose. The purpose of this research is to look into the use Analysis of Badminton Techniques Smash Using A Biomechanical Approach. Materials and methods. The PRISMA standards for systematic reviews and meta-analyses were followed in this review investigation. The study must be published with in the prior four years, from January 2020 to Desember 2024. In the search procedure, the following keywords are used: (1) Badminton; (2) Smash. Scopus search engine was used in this research. Results. The theme of this research as a whole obtained 155. Consists of 37 articles which are then taken 10 relevant articles. Conclusions. Analysis of badminton smash techniques using a biomechanical approach includes the effect of smash techniques with a biomechanical approach based on relevant results includes improving smash performance, strength and speed training, muscle strength biomechanical, improving smash speed, glutamine accelerates athlete recovery, and fatigue reduces jumping smash performance